2019
DOI: 10.3390/biom9100550
|View full text |Cite
|
Sign up to set email alerts
|

Brusatol, a Nrf2 Inhibitor Targets STAT3 Signaling Cascade in Head and Neck Squamous Cell Carcinoma

Abstract: STAT3 is a latent transcription factor that plays a vital role in the transmission of extracellular signal from receptors to the nucleus. It has been regarded as a master transcription factor due to its role in the regulation of a broad spectrum of genes, which can contribute to oncogenesis. Persistent activation of STAT3 and deregulation of its signaling has been observed in various human cancers including head and neck squamous cell carcinoma (HNSCC). In the present work, we identified brusatol (BT) as a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 84 publications
(90 reference statements)
0
46
0
Order By: Relevance
“…In addition, TGFβ-induced EMT is also dependent on JAK-STAT3 cascade in lung cancer [87] . In our previous investigation, we identified that STAT3 signaling can be downmodulated by BT in HNSCC cells [38] . Here we found that BT suppressed the phosphorylation of STAT3 Y705 in HCC cells that can contribute to its effect on various hallmarks of cancer, specifically EMT.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, TGFβ-induced EMT is also dependent on JAK-STAT3 cascade in lung cancer [87] . In our previous investigation, we identified that STAT3 signaling can be downmodulated by BT in HNSCC cells [38] . Here we found that BT suppressed the phosphorylation of STAT3 Y705 in HCC cells that can contribute to its effect on various hallmarks of cancer, specifically EMT.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, Yang et al described the effect of BT on various types of cancer cells, Nrf-2-guided gene transcription, and glutathione de novo synthesis [37] . In our previous report, we had reported that BT can effectively abrogate STAT3 phosphorylation in head and neck squamous cell carcinoma (HNSCC) cells, but did not analyze its actions on EMT process and tumor growth in preclinical settings [38] . Since, STAT3 is an inducer of EMT, we have assessed here whether the influence of BT on EMT may be mediated through the modulation of STAT3 in a HCC model.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, searching for new agents, including natural compounds or suitable delivery strategies to increase the cancer specificity and avoid undesirable effects, remains a great challenge. Several natural compounds showed the ability to inhibit STAT3 activation, leading to downregulation of survival genes, cell cycle arrest and apoptosis and also potentiating the cytotoxic effects of anticancer drugs [22,23,[99][100][101][102][103][104][105]. Among them, curcumin exhibited anti-cholangiocarcinoma effects by the suppression of different transcription factor cascades, among which STAT3, NF-kB and AP-1 [106].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of STAT3 has been reported to potentiate growth, survival, and chemo-and radio-resistance of NSCLC [81,82] and human squamous cell carcinoma cells [83,84]. A significant correlation was found between STAT3 protein expression and tumor differentiation, clinical stage, and lymph node metastasis of NSCLC patients [85].…”
Section: Discussionmentioning
confidence: 89%